Simultaneous Bilateral Cochlear Implantation in Very Young Children Improves Adaptability and Social Skills: A Prospective Cohort Study. Issue 2 (20th September 2022) - Chen, Ying; Li, Yun; Jia, Huan; Gu, Wenxi; Wang, Zhaoyan; Zhang, Zhihua; Xue, Minbo; Li, Jingjie; Shi, Wentao; Jiang, Linlin; Yang, Lu; Sterkers, Olivier; et al.
Abstract : Objectives: To investigate the value of using the Gesell Development Diagnosis Scale (GDDS) to predict developmental outcomes in very young children who undergo simultaneous bilateral cochlear implantation. Design: In this prospective cohort study, a repeated-measures investigation was conducted in a tertiary referral hospital. A total of 62 children receiving simultaneous bilateral cochlear implantations were enrolled from April 2017 to August 2018. They were divided into 2 groups depending on the operative age: "Infants" group (6 to 12 months, N = 38) or "Children" group (12 to 36 months, N = 24). Data on the surgical outcomes, auditory development, speech production, and developmental indicators were collected until 2 years after the initial fitting. The primary outcome measure was the GDDS, a neuropsychological development examination. Secondary outcomes included the following: complication rate, aided pure-tone average, Infant-Toddler Meaningful Auditory Integration Scale, Categories of Auditory Performance-II, Meaningful Use of Speech Scale, Speech Intelligibility Rating, and the LittlEARS Auditory Questionnaire. Results: The mean ages at implantation in infants and children groups were 9.2 ± 1.17 and 16.6 ± 3.60 months, respectively. Significant differences were found in the social skills ( p = 0.001) and adaptability ( p = 0.031) domains of GDDS. The younger the age of bilateral cochlear implants surgery, the higher developmental quotient of language, social skills, and adaptability the child could achieve after 2 years. The complication rates in the infants and children groups were 0% versus 2.1% ( p = 0.57). There was no surgical complication in the infants group. In the children group, 1 case with enlarged vestibular aqueduct and Mondini malformation had a receiver-implant misplacement on the right side (2%, 1/48). In the two groups, auditory performance and speech production had improved similarly. In the infants group, social skills developmental quotient at baseline had a significant positive relationship with Meaningful Use of Speech Scale after 2 years. Conclusions: Simultaneous bilateral cochlear implantation in younger children improves adaptability and social skills. GDDS is a sensitive tool of evaluating short-term effect of bilateral cochlear implants in neuropsychological development and constitutes a reliable predictor of speech production for the very younger pediatric cochlear implant users.